Peningkatan Pemahaman Peduli Lingkungan Dengan Aksi Bersih Pantai Pasia Jambak - Engrina Fauzi; Diva Angraini; Aziza Putri; Asih Kayrani; Hawayunedia, Hawayunedia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The beach cleanup activity is a concrete manifestation of students' contribution to preserving the environment. This activity was carried out at Pasia Jambak Beach, Padang, with the aim of raising public awareness about the importance of clean beaches as tourist areas and habitats for marine life. The activity was attended by students of the Communication Studies and English Literature Study Programs at Dharma Andalas University, through a series of preparation stages until the direct implementation. Based on the results of the activity, plastic waste dominated the type of waste found, which has the potential to pollute the environment and endanger marine life. In addition to improving the condition of the beach to be cleaner and more beautiful, this activity also succeeded in fostering a spirit of mutual cooperation and increasing social awareness. This action is expected to inspire people to continue to protect and care for the coastal environment sustainably.